The Role of Jordanian Universities in the Development of Educational Services Outcomes Quality - Zakariya A. M. Azzam (University of Science and Technology, Yemen, 2014)
The Role of Jordanian Universities in the Development of Educational Services Outcomes      QualityAbstract: Quality in the field of education is considered an important issue which forces Educational Institutions to adopt such issue in order to achieve a distinctive results in its operations which ensure effective output of such Institutions. The present study aimed to realize the Role of Educational Institutions in Developing The Quality of Educational Services Output in Jordan. Such quality dimensions may foster the quality of educational services which can be suitable for market requirements. The researcher developed five main hypotheses which is based on quality of educational services dimensions approved internationally which are: Management Commitment towards quality, Continuous development and improvement, physical environment, social responsibility and Technological tools adopted by educational institutions. The researcher assumed that there is a statistical significance between the above mentioned dimensions and the quality of higher educational output. To collect the necessary data the researcher designed a self-administered questionnaire, which was distributed personally on the selected sample of Jordan Universities. The researcher distributed 75 questionnaires and recollected only 66 suitable for statistical analysis. Finally, the study shows that there is a statistical relationship between all the dimensions and the quality of educational output in Jordan Universities. Keywords: Quality, Higher Education, Educational service, Jordan, Higher Educational Output.